Nutritional status of adult hemodialysis patients in Al-Najaf Al-Ashraf Governorate - Kadhum, Ibrahem; Mohammed, Widad (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To assess the nutritional status of hemodialysis patients.Methodology: A descriptive quantitative cross sectional study was effectuated in hemodialysis centers fromFebruary 2011 to September 2011. A purposive "non-probability" sample of (70) male and female hemodialysispatients in al-Najaf al-Ashraf Governorate from those who have spent more than six months on maintenancehemodialysis schedule. Data collected through using of a well-designed questionnaire consist of five parts, partone consists of sociodemographic contain (9) items, and part two consists of medical data contain (8) items, andpart three consists of health and nutrition behavior contain (12) items plus (8) items of anthropometricmeasurements, and part four consists of food frequency contain (5) major items, and part consist of laboratoryinvestigation contain (9) items. In addition to food diary (24 hour dietary recall) used for validating the foodfrequency part. Data collected by direct interview method with ESRD on maintenance hemodialysis patients’ alsoby anthropometric measurement method and blood sample for laboratory investigation. Reliability of thequestionnaire was determined through pilot study and validity determined through a panel of experts consists of(18) experts. Data was analyzed by using of descriptive data analysis (frequencies, percentages, mean, standarddeviation and relative sufficiency) and by using of inferential analysis (correlation coefficient, t- test and χ²).Results: The study results indicates that the majority of study sample suffer from moderate malnutritionaccording to several indicators including anthropometric measurements, laboratory investigations and (type andquality) of food. Most of study sample was illiterate, and the sample divided between male and female withinvisible variance between percentages, the majority of study sample was nutritionally instructed but they don’treflect the desired compliance.Recommendations: The study recommends with the necessity of establish a nutritional health style forhemodialysis patients including several dialogist like calibrating of dietary intake, increase physical exercise astolerated, control body weight and enrich the list of laboratory investigations. Workout anew studies about thestudied phenomenon, activate the role of dietician (doctor and nurse) in hemodialysis centers, hemodialysismalnutrition alert day and initiate a proper financial support through establish a hemodialysis malnutritionfoundation work for improvement of socioeconomic status and nutritional status through study subjects